ANALISIS PENGARUH MEDIA PEMBELAJARAN TERHADAP MINAT BELAJAR SISWA SEKOLAH DASAR - Barokah, Awalina; Farahdila, Farahdila; Syahputra, Farid Ilham; Rahayu, Sri (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2024)
Teaching media is a tool whose function is relevant to use when presenting learning materials in the world of education. However, educators must know what impacts the use of learning media has on students' learning interest. The use of learning media that is relevant, effective, fun, interesting and gives meaning to students is one learning method. Learning media is used to make it easier for educators to convey the content of the material to be delivered so that learning is more efficient and effective. This research aims to determine the effect of using learning media on students' interest in learning, aimed at elementary school level. The research method used is literature study. The data collection obtained was obtained through reviewing and analyzing journals, books, articles and e-books that were related to the titles taken. The results of this research indicate that there is an influence of the use of learning media on elementary school students' interest in learning.